2021
DOI: 10.3389/fcvm.2021.760320
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-Domain Characteristics Response to Passive Exercise in Patients With Coronary Artery Disease

Abstract: Purpose: The enhanced external counterpulsation (EECP), a kind of passive exercise, is a novel non-invasive therapy used to improve peripheral perfusion in patients with coronary artery disease (CAD). However, whether frequency-domain characteristics of peripheral hemodynamics may benefit from passive exercise needs to be verified.Methods: We recruited 21 patients with CAD and 21 healthy controls in this study. Ultrasonic blood flow velocity spectrum in left carotid (LC) and right carotid (RC) common arteries,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…While EECP reduced amplitude and frequency characteristics in the carotid arteries, the energy ratio characteristics in the left carotid and right brachial arteries displayed an opposite response during EECP between CAD patients and controls 9 .…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…While EECP reduced amplitude and frequency characteristics in the carotid arteries, the energy ratio characteristics in the left carotid and right brachial arteries displayed an opposite response during EECP between CAD patients and controls 9 .…”
Section: Introductionmentioning
confidence: 75%
“…mean inner diameter, blood flow velocity and resistance index) and frequency-domain characteristics (e.g. amplitude and energy ratio) between CAD patients and controls 8,9 . However, we found that a single indicator analysis may not affect the significant differences between the two groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation